Endomicroscopy of the Pancreaticobiliary System. (14th February 2013) - Peter, Shajan; Bang, Ji Young; Mönkemuller, Klaus; Varardarajulu, Shyam; Wilcox, C. Mel
Abstract : It is often difficult to accurately differentiate between benign and malignant pancreaticobiliary strictures, and some are interpreted as indeterminate despite ERCP, EUS, or radiological imaging techniques, thereby making it difficult for the clinician to make appropriate management decisions. Probe-based confocal laser endomicroscopy (pCLE) is an innovative imaging tool integrating real-time in vivo imaging of these difficult-to-interpret strictures in the pancreaticobiliary system during endoscopy. Recent studies of endomicroscopy have shown a promising role with improved accuracy in distinguishing these lesions, thus paving the way for future research addressing improving precise interpretation, training, and long long-term impact.